2003
DOI: 10.1021/es034392w
|View full text |Cite
|
Sign up to set email alerts
|

Critical Evaluation of Desorption Phenomena of Heavy Metals from Natural Sediments

Abstract: In natural sediments, the majority of heavy metal ions are generally associated with the solid phase. To become bioavailable, the metal ions must desorb from the solid. Numerous studies of heavy metals in sediments have suggested that sorption and desorption exhibit hysteresis (i.e., the two processes are not reversible), while other studies have suggested that desorption hysteresis does not exist. In this study, sorption/desorption hysteresis of lead (Pb) and cadmium (Cd) was evaluated over the following rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…In the literature, the term hysteresis is often used as an equivalent to some degree of irreversible sorption behavior, which implies a non-equilibrium transfer of contaminants between solution phase and mineral surfaces (e.g., (Laird et al, 1994;Gao et al, 2003;Sander et al, 2005)). Under constant solution conditions, the contaminant fraction that remains sorbed after desorption equilibration is often larger than the one during the initial (ad)sorption step.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the term hysteresis is often used as an equivalent to some degree of irreversible sorption behavior, which implies a non-equilibrium transfer of contaminants between solution phase and mineral surfaces (e.g., (Laird et al, 1994;Gao et al, 2003;Sander et al, 2005)). Under constant solution conditions, the contaminant fraction that remains sorbed after desorption equilibration is often larger than the one during the initial (ad)sorption step.…”
Section: Introductionmentioning
confidence: 99%
“…Although sediment sorbs heavy metals and restrains their mobility under favorable conditions, previous studies have reported that sediment-sorbed heavy metals are released into the water body according to the changes in environmental conditions (i.e., pH, redox potential, ionic strength, etc. ), and consequently the free metal ions accumulate in aquatic organisms and exhibit their toxicity [3][4][5][6]. Unlike soil and groundwater remediation, sediment remediation technologies that are effective and proven in the field are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Thus a majority of TEs are associated with the solid phase of soil where they occur as precipitate or co-precipitate of mineral salts. Co-precipitation usually occurs with newly formed chemical species such as carbonates, phosphates, oxides and hydroxides [24,25]. These kinds of co-precipitation help to limit exposure of toxic TEs to biota, and also slow down the release of TEs into the soil solution.…”
Section: Nutrient Cycle and Plant Uptake Of Tesmentioning
confidence: 99%